2021
DOI: 10.1016/j.ijid.2021.07.034
|View full text |Cite|
|
Sign up to set email alerts
|

Propensity-Score Analysis Reveals that Sex is Not a Prognostic Factor for Mortality in Intensive Care Unit-Admitted Patients with Septic Bacteremia

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…It has been found that sex could affect the manifestation and pathophysiology of many diseases ( 9 11 ). The impact of sex on outcomes in patients with sepsis has been widely investigated, yielding conflicting results ( 35 38 ). It has been found that women generally have more advantageous immunological responses compared to men by the effect of their sexual hormones ( 13 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that sex could affect the manifestation and pathophysiology of many diseases ( 9 11 ). The impact of sex on outcomes in patients with sepsis has been widely investigated, yielding conflicting results ( 35 38 ). It has been found that women generally have more advantageous immunological responses compared to men by the effect of their sexual hormones ( 13 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies specifically designed to avoid sample bias are needed to validate this result. It is generally assumed that men had a higher incidence of sepsis, but the research about the relationship between sex and sepsis prognosis failed to reach consistent conclusions ( 35 38 ). Ponce-Alonso et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex related differences in ICU admission, treatments offered, and outcome is becoming an increasing topic of interest. However, one Spanish study of 440 patients admitted to ICU with BSI found no differences in outcome by sex once confounding factors were adjusted for using propensity matched analysis [34]. The duration of treatment for patients with BSI admitted to ICUs has been an ongoing debate.…”
Section: Outcome Treatment and Costmentioning
confidence: 99%
“…Nachtigall et al found a higher mortality risk in hospitalized male patients older than 60 years with COVID-19 [5]. In contrast, Ponce-Alonso et al found no effect of sex on mortality in patients with sepsis [6]. The effect of sex on patient treatment in emergency departments and ICU is measurable and was demonstrated by Valentin et al for therapeutic interventions and outcomes in the critically ill [7][8][9].…”
Section: Introductionmentioning
confidence: 99%